Coexistence of Femoroacetabular Impingement and Snapping Hip Due to Osteochondroma of the Femoral Neck - a Case Report - Loures, Elmano de Araújo; Pereira, Felipe Jader Coelho; Loures, Daniel Naya; Mendes Júnior, Adriano Fernando (International Journal of Orthopedics and Rehabilitation, 2018)
Introduction and objectives: The aim of this report is to highlight the uncommon association of femoroacetabular impingement and snapping hip due to an osteochondroma of the femoral neck. Case report: a 41 years old male patient complaining progressive pain, limited range of motion and snapping hip with audible click for more than five years was diagnosed with an association of different conditions affecting his right hip joint and surgical treatment was indicated with good outcome in one year follow-up. Conclusion: The authors pointed out the rare association of these conditions in the same joint and the need of correct interpretation of radiological and clinical findings for diagnosis, surgical planning and satisfactory resolution of symptomatology, leading to recovery of the individual’s functional capability.